Academic Nurse Educators’ Perceptions of Classroom Assessment Practices as Means for Quality Nursing Education - C.E Oguguo, Basil; U. Ene, Catherine.; O. Dave-Ugwu, Priscilla; I. Ezechukwu, Rosaline.; I. Okebanama, Cliff; Ukala, Geoffrey; J. Agugoesi, Oluchi; C. Ugwu, Felicia (International Journal of Psychosocial Rehabilitation, 2024)
Assessment is considered a challenging task; to this effect, in order to have an efficient classroom assessment, an adequate understanding and mastery of assessment practices is needed by nurse educators. Nurse Educators’ are very essential in implementing the right assessment approaches since they possess the necessary assessment practices such as their attitudes, values, and beliefs etc. The study sought to gain an understanding of the extent to which Nurse Educators’ use different classroom assessment tools to understand and support both the teaching and learning processes in undergraduate studies. Descriptive survey research design was employed and 397 Nurse Educators participated in the study. The instrument used for data collection was ‘Bloom’s Cognitive, Affective, and Psychomotor BehavioursQuestionnaire’ (BCAPBQ) with 43-items. The internal consistency of the instrument was determined using Cronbach’s Alpha and the reliability index of 0.81 was obtained. The study discovered thatnurse educators to higher extent perceived the levels of behavioural objectives as means for providing quality nursing education. The findings also showed the extentnurse educators’ assessment practices measure each levels of Bloom’s Taxonomy behaviours.The findings support previous findings of authors who found that teachers’ perceptions of classroom assessment affected their classroom assessment practices.The findings of this study will lead to a broader scale with the basic data it supplies. It will expose the nurse educators to different strategies used in monitoring undergraduate students’ nurses learning. The research supplies good idea of the instruments for measuring those staked learning outcomes in nursing education.